2039. Antibiotic Stewardship in Burn and Chronic Wound Centers in Nepal - Nauriyal, Varidhi; Dhoj. Joshi, Rajesh; Raj Poudel, Suresh; Banstola, Laxman; Joshi, Anip; Acharya, Arjun; Bahadur Thapa, Buddhi; Shrestha, Basudha; Maki, Gina; Shakya, Malika; Man. Joshi, Nilesh; Karki, Kshitij; et al. (Open forum infectious diseases, 2019)
Background Data surrounding antibiotic stewardship (AMS) in burn and chronic wound centers in low- and middle-income countries (LMIC) are limited. Given the long-term nature of the wounds, increased risk of infection and the potential for further infections being treated with antibiotics, burn and chronic wound centers represent a unique opportunity for antimicrobial stewardship. Methods Three hospitals that maintain long-term burn or chronic wound wards were selected in two regions in Nepal. A post-prescription review and feedback program (PPRF) was instituted in these departments, and locally salient antibiotic practice guidelines were developed based on international and local standards by the research team and local experts. Chosen physicians at each facility were trained as master physician champions. Champions subsequently trained physicians in their wards and ensured that guidelines were followed by prescribing physicians. Baseline and post-intervention phases covered 5 months each during 2018–2019. During the post-intervention phase, physician champions reviewed antimicrobial use at 72 hours and made one of the three recommendations if the antibiotic course was deemed unjustified: changing the antibiotic, stopping the antibiotic course, or de-escalation of the antibiotic. Results 482 patients were enrolled throughout the duration of the study, with 241 patients in each of the baseline and post-intervention periods. The average length of stay was 8.0 days in baseline (range 3–48 days) vs. 6.4 days (range 3–70 days) during post-intervention. Between baseline and post-intervention, IV antibiotics decreased from 1,161 antibiotic-days per 1,000 patient-days (PD/1,000) to 1,137 PD/1,000. Oral antibiotics decreased from 101 PD/1,000 to 77 PD/1,000. In addition, cephalosporins decreased from 526 PD/1,000 to 474 PD/1,000, and aminoglycosides decreased from 264 PD/1,000 to 117 PD/1,000. Conclusion Appropriate antimicrobial use is vital in patients with a long length of stays in the hospital to reduce the development of multi-drug-resistant organisms. This intervention showed that a post-prescription review and feedback model can have impact in chronic wound and burn centers in Nepal and be further adapted for use in other LMIC. Disclosures All authors: No reported disclosures.